Assessment of ventricular elements of mitral valve by left ventriculography. - Boucek, R J (1977)
In the left ventriculogram in the right anterior oblique projection the plane of the mitral valve is seen in profile and the papillary muscle shadows are outlined. The distance from the middle of the papillary muscles to the plane of the mitral valve during systole was used to assess the average length of the chordae tendineae, and the area of the papillary muscle shadows was measured as an index of hypertrophy in a series of hearts with mitral valve disease. Valvar mitral stenosis is characterised by slight reduction in the length of chordae tendineae and more hypertrophy of the papillary muscles, while in subvalvar mitral stenosis there is more shortening of the chordae tendineae and less papillary muscle hypertrophy. Valvotomy may lengthen the chordae tendineae in subvalvar mitral stenosis. In rheumatic mitral regurgitation length of chordae tendineae and papillary muscle size were normal. The measurements were not useful in assessing non-rheumatic mitral regurgitation.